BALI DI TENGAH PANDEMI COVID-19: STUDI KUALITATIF TERHADAP PELAKU PARIWISATA DI WILAYAH KUTA, BALI - Rindo Bagus Sanjaya (JURNAL MASTER PARIWISATA, 2023)
Kuta is a region located in Badung Regency, which has the highest number of workers in the tourism industry in Bali. Despite this, the Covid-19 pandemic has had a significant economic impact on both workers and tourism operators in Kuta. This is evidenced by reduced working hours, layoffs, closures of tourism-related businesses, and slowdown in the economy in Kuta. The objective of this study is to explore how tourism industry players in Kuta have conducted their activities before, during, and after the pandemic. The study adopts a qualitative research methodology, utilizing in-depth interviews with tourism actors and workers in Kuta from various backgrounds, such as hotel owners, surfing instructors, hotel staff, guest house and laundry owners, travel agents and tour guides, online motorcycle drivers, motorbike rental owners, and souvenir traders. The findings of the study reveal that every business actor and worker in the tourism sector has their own approach to cope with the Covid-19 pandemic. Keywords: tourism resilience, covid-19 pandemic, tourism workers, Kuta Bali.